Responses of milk urea nitrogen content to dietary crude protein level and degradability in lactatingHolsteindairy cows - S.W. Zhai; J.X. Liu; Y.M. WU; J.A. YE; Y.N. XU (Czech Journal of Animal Science, 2006)
Two experiments were conducted to investigate the effects of dietary crude protein level and degradability on milk urea nitrogen (MUN) content. In experiment 1, twelve multiparous lactating cows averaging 176 days in milk were divided according to DIM and milk production into three 4 × 4 Latin squares with four 2-week periods. Cows were fed four diets with different crude protein levels (13.0, 14.0, 15.0, and 16.0%, DM basis) with isocaloric, respectively. Crude protein levels had a low effect on milk yield and composition (P > 0.05), but a significant effect on MUN content. There were significant differences in the MUN content of cows fed either of the two diets (P < 0.01). In experiment 2, fifteen multiparous Holstein dairy cows averaging 91 days in milk were classified according to DIM and milk production into five 3 × 3 Latin squares with three 3-week periods. Cows were fed one of the three isocaloric and isonitrogenous diets with RUP being 30.8%, 36.2%, and 41.6% (CP basis), respectively. Milk yield, milk composition, and MUN content were not significantly affected by protein degradability, and there were no significant differences between any two dietary treatments (P > 0.05). These results indicated that MUN might be used as a parameter to monitor the change in dietary protein levels.